Biphasic crude palm oil dechlorination: Effect of volume ratio and concentration of sodium silicate to hydroxide ion distribution - Hari, Zulfa Kurnia Umani; Syamsul Bahari, Abdullah; Saidatul Shima, Jamari; Che Mat, Che Rahmat; Mohd Sabri, Mahmud (IIUM, Malaysia, 2024)
Dechlorination of crude palm oil (CPO) to prevent toxic contaminant formation inspired studies of applying alkaline in its treatments. This paper reports distribution of hydroxide ion (OH-) from sodium hydroxide (NaOH) and sodium silicate (SS) between aqueous solution and CPO under equilibrium systems to moderate its presence in CPO and minimize saponification. In this study, OH- was determined through pH measurements, which also indicated sodium hydroxide (NaOH) presence. Filtered CPO was mixed with SS solution at room temperature in various volume ratios and SS concentrations under 800-rpm agitation before being settling down to form layers of liquids. The One-Factor-in-A-Time approach was used to optimize the ratio. Acid value test and GCMS analyses were used to determine free fatty acids. Calibration curve construction revealed 0.0818 of OH- dissociation constant. SS solution could turn to acidic at 6.344 × 10-5 g/ml of concentration probably due to hydrated silica. Using 0.01 g/ml SS solution, volume ratios between CPO and SS solution spanning from 0.33 to 3 were all under alkaline conditions but decreasing OH- concentration, where 2 liquid phases only appeared in the ratio of 2.33 and 3. Concentration of SS was then varied for the 2.33 volume ratio and a sigmoid trend of OH- increase was evident. The McCabe-Thiele plot revealed hydroxide ion equilibrium below operating line suggesting its extraction impossibility to CPO.